1961
DOI: 10.1084/jem.113.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Endotoxins on Metabolism

Abstract: Endotoxins can be assayed on the basis of their toxicity for experimental animals, their pyrogenicity, their ability to necrotize tumors, and their antigenicity. Another property, observed in the course of recent experiments, makes possible a new assay. The initial observation on which the assay is based was obtained when an intraperitoneal injection of appropriate numbers of heatkilled cells of Salmonella typhimurium was found to prevent completely the elevation in urinary nitrogen excreted by mice given adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1961
1961
1986
1986

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Endotoxins.--As in previous reports (8,9), the standard material employed as endotoxin is a saline suspension of heat-killed (pasteurized) Salmonella typhimurium, strain SR-11. A sutticient quantity of material for several months of work is prepared, dispensed in sealed tubes in 10 ml portions, and stored at 5°C until ready for use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endotoxins.--As in previous reports (8,9), the standard material employed as endotoxin is a saline suspension of heat-killed (pasteurized) Salmonella typhimurium, strain SR-11. A sutticient quantity of material for several months of work is prepared, dispensed in sealed tubes in 10 ml portions, and stored at 5°C until ready for use.…”
Section: Methodsmentioning
confidence: 99%
“…Irrcversibility of Endointoxication.--It has been found that cortisone (and other glycocorticoids) have prophylactic value against endotoxin but are unable to protect against lethality after a delay of a few hours (9). Endointoxi-cation appears to be irreversible, therefore, as far as cortisone is concerned.…”
Section: Protection Of Mice Against E Cotl I2popolysaccharide ~Ith Cmentioning
confidence: 99%
“…It has been found that cortisone (and other glycocorticoids) has prophylactic value against endotoxin but is unable to protect against lethality after a delay of a few hours (Berry and Smythe, 1961). Endointoxication appears to be irreversible, therefore, as far as cortisone is concerned.…”
Section: Irreversibility Of Endointoxicationmentioning
confidence: 99%
“…(Received for publication, July 19, 1961) An injection of either heat-killed Salmonella typMmurium or the lipopolysaccharide from any one of several different Gram-negative bacteria prevents or lowers, depending upon dosage, the increase in urinary nitrogen excreted by mice in response to an injection of adrenocorticotrophic hormone (ACTH) (1). All available evidence points to the fact that endotoxin is responsible for this effect and that the quantity required is inversely proportional to the toxicity of the specific preparation employed.…”
Section: (From the Department Of Biology Bryn Mawr College Bryn Ma~z)mentioning
confidence: 99%
“…The particular material employed had an LD60 of 1.5 mg when injected intraperitoneally into 20 gm mice (1). In some cases a purified lipopolysaccharide derived from Escherichia coli was employed.…”
Section: Determination Of In Vitro Secretion Of Corticoids By Adrenalmentioning
confidence: 99%